IMPACT OF VOCATIONAL STUDIES ON STUDENTS’ CREATIVITY IN THE DUAL-OPERATIONAL CURRICULA APPROACH OF A UNIVERSITY EDUCATION FOR SUSTAINABLE DEVELOPMENT (NAU Journal of Technology and Vocational Education, 2026)
In Nigeria, policy guidelines bordering on vocational and technical education have increased the attention on the field in the existing educational institutions. Focus on one course or double major course is uncommon in Nigerian higher institutions. However, the operation of a dual system of education with significant attention to specialised disciplines and vocational studies simultaneously in some countries of the world, including Nigeria, caught the attention of the researchers. The need therefore arises to examine the impact of vocational studies on students’ creativity in the dual-operational curricula approach in a university education for sustainable development. Descriptive survey research design guided by three research questions was used for the study, and five hundred final year students randomly selected across five out of the six Colleges in the then Tai Solarin University of Education, now Tai Solarin Federal University of Education situated in Southwestern Nigeria participated in the study. Vocational Studies Creative Impact Scale (VSCIS) (r=0.75) was used for data collection. Frequency count, percentages, mean and chart were used for data analysis. The results, showed that the implementation of the dual-operational curricula approach influences the creativity of the students. Among the recommendations put forward is the need to reinvigorate the dual-operational curricula approach with constant provision of resources and adequate practical delivery mode system for sustainable development prospects of Nigerian university students.
Keywords: Creativity; Dual-Operational Curricula; Vocational Studies